Penerapan Model CTL dalam Meningkatkan Hasil Belajar Materi Haji dan Umrah pada Siswa Kelas VI SD IT Sairussalam - Khairatun Nisa Pohan; Mukhsin Nyak Umar; Yusra Jamali (Tadabbur: Jurnal Peradaban Islam, 2023)
This study aims to investigate the application of the Contextual Teaching and Learning (CTL) learning model in improving the learning outcomes of Hajj and Umrah materials in class VI students of SD IT Sairussalam. The research method used is qualitative research with a case study approach. The research participants involved 30 grade VI students who were studying hajj and umrah material. Research data was collected through class observations, interviews with teachers, and documentation of student learning outcomes. Data analysis was carried out through the process of data reduction, data presentation, and drawing conclusions. The results of the study show that the application of the CTL model effectively improves the learning outcomes of Hajj and Umrah materials in class VI students. In applying the CTL model, the teacher uses a contextual approach that pays attention to the real-life context of students in presenting hajj and umroh material. Teachers also integrate various relevant learning resources and involve students in interactive and collaborative learning activities. In addition, the teacher provides regular feedback to students to help them improve their understanding and skills in hajj and umrah material.